Atividade das enzimas NTPDASE e 5 - nucleotidase em plaquetas de gestantes normais e de alto risco - Leal, Claudio Alberto Martins (2006)
Hemostasis is a complex process that involves equilibrium between the coagulation and fibrinolytic systems. Furthermore, the spatial and temporal expression of NTPDases in the vasculature appears to control platelet activation, thrombus size and stability, by regulating phosphohydrolytic activity and consequent P2 receptor signaling. Here we show the activity of ectonucleotidases on the platelet surface of normal pregnant women and pregnant women with complications. The activities of the enzymes, NTPDase and 5 - nucleotidase, were analyzed in the platelets of four patient groups composed of women divided into the following way: nonpregnant (NP), pregnant without complications (P), pregnant with hypertension (HP) (preeclampsia) and pregnant with gestational diabetes mellitus (GDP). Increased NTPDase and 5 -nucleotidase activities were observed in the groups of P, HP and GDP when compared to control (p<0.01). Ectonucleotidase activity in platelets from group P, HP and GDP were enhanced, showing that pregnancy with and without complications enhanced ATP, ADP and AMP hydrolysis. This fact is very important to corroborate with the thromboregulatory role of this enzyme in physiological and pathological conditions.